Public–Private Partnership: A Bridge between Public and Private Sector - Jermsittiparsert, Kittisak; Thanh Nguyen, Phong; Thuy To Nguyen, Quyen Le Hoang; Bich Huynh, Vy Dang; Shankar, K. (Opción, 2019)
To operate, finance and develop a project like convention centers, parks and public transportation networks the collaboration of company of private sec- tor and government agency is known as Public-private partnerships (PPP). A project can take less time when it financing through public private net- work. This Public private network provides a bridge between public and pri- vate sectors. This partnership is important for developing several business aspects.